Building Information Modelling (BIM) usage among construction professionals in Lagos State, Nigeria - Ibrahim, Abdullah Suleiman; Abdul-Hameed , Taofeek A.; Morakinyo, Kolawole Opeyemi; Taiwo, Richard Oluseyi (Local Engineering, 2025)
Building Information Modelling (BIM) has become a popular subject amongst professionals in the architecture, engineering, and construction (AEC) industry. As Nigeria develops technologically, the use of building information modeling (BIM) in delivery of building and infrastructure projects cannot be overemphasized, as it is a well-known innovative approach in project design and construction. Building information modeling (BIM) is a process of developing a virtual equivalent of the actual building that supports data exchange, management and communication during the whole building’s life cycle. The BIM software gives a digital representation of how the building will be after construction. This study provide insight into Building Information Modelling (BIM) Usage among construction professionals in Lagos State. The study adopted a pragmatic research technique that uses both qualitative and quantitative research approaches. Qualitative (secondary) data were extracted from literature and analyzed by content analysis. While quantitative (primary) data were gathered with a structured questionnaire. The primary data were collected from 252 construction professionals in the study area. This study considered level of awareness of BIM, and extent of usage of BIM in the Nigerian building construction industry; respondents’ perceived benefits of building information modeling (BIM); BIM Usage rates among construction Professionals in Lagos State; Challenges Impeding the Adoption and Usage of BIM in construction industry, Respondents’ perceived barriers to the adoption of BIM in the Nigerian construction industry. A total number of 300 questionnaires were administered systematically to professionals in Lagos, resulting in 252 valid responses analyzed for the purpose of the study. The collected data were analyzed using Statistical Package for Social Science (SPSS) – Version 20 and Microsoft Analysis. Descriptive analysis techniques, such as frequency, percentage, mean item score, and relative importance index (RII). As a contribution to knowledge, the paper has established that there is a high level of knowledge of Building Information Modeling (BIM) in the Nigerian Construction Industry which is associated to the high level of awareness and utilization amongst stakeholders. The paper concludes with policy recommendations to promote BIM adoption in Nigeria, including financial incentives, training programs, and awareness campaigns. This study underscores the potential of BIM to revolutionize the Nigerian construction industry by addressing inefficiencies and improving project delivery outcomes.